Insurance-Markets Equilibrium with Double Indivisible Labor Supply - Aleksandar Vasilev (Czech Economic Review, 2015)
This note describes the lottery- and insurance-market equilibrium in an economy with both private and public sector employment and non-convex labor supply. In addition, when households are constrained to search for jobs only in a certain sector, the framework requires that there should be separate insurance markets: a public and a private sector one, which would pool the unemployment risk of the corresponding group of households. The unemployment insurance market segmentation is a new result in the literature and a direct consequence of the non-convexity of the labor supply in each sector and the sorting effect of the sector-type shock introduced in the model setup.
Keywords: H31; J21; 330; indivisible labor; public employment; insurance